PELATIHAN PEMBUATAN SABUN CUCI PIRING DI DUKUH MOJO DESA PRINGANOM - Susilowati, Endang; Gusnadi , Aloisius Satriya; Rohmansyah , Krisna; Purnomo, Diky Eko; Widyawati , Eliana; Hidayah , Luthfi; Assalim , Nafila Saniya; Luthfiyani , Fadiyah; Murjono , Hodia Harywan; Cahyaningtyas , Sherlyna (Inspirasi: Jurnal Pengabdian Masyarakat, 2024)
Soap is a cleaning agent made from a chemical reaction between fats derived from plant or animal oils and an alkali (such as sodium hydroxide or potassium hydroxide). One type of soap that is commonly used in daily activities is dish soap. The increased use of dish soap has led to higher sales, prompting the development of a dish soap making training program as an effort to address the economic challenges faced by the community. The target audience for this dish soap making training is homemakers in Dukuh Mojo, Desa Pringanom, Kecamatan Masaran, Kabupaten Sragen. The training method, which includes preparation, implementation, and evaluation, is designed to ensure a thorough understanding and effective application of the material taught. This training is expected to provide new insights for the community and create new business opportunities for homemakers to sell their own dish soap as a local product, potentially generating new job opportunities for themselves and the surrounding community.